Temperature / mechanical dual response type drug controlled release hydrogel and preparation method thereof
By preparing a temperature/mechanical dual-responsive drug-controlled release hydrogel, the problems of precision and controllability of hydrogel drug release systems have been solved, enabling efficient and safe local administration of drugs such as ketoprofen for pain and inflammation, while reducing systemic toxic side effects.
Patent Information
- Application Number
- CN202510961746.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-12-05
AI Technical Summary
Existing hydrogel drug delivery systems lack precision and controllability, making it difficult to meet the clinical need for efficient and safe delivery, especially in the treatment of pain and inflammation such as ketoprofen, where traditional administration methods may cause systemic toxic side effects.
A method for preparing temperature/mechanical dual-responsive drug-controlled release hydrogels was adopted. After dissolving NIPAm, AAc and crosslinking agent, SDS was added, followed by the addition of initiator and promoter to form MGV microgels. These microgels were then mixed with hydrophobic drugs and finally crosslinked with NIPAm monomers to form NMK hydrogels, thus achieving controlled drug release.
The prepared hydrogel has excellent mechanical properties and biocompatibility, and can precisely release drugs through a dual temperature/mechanical response, reducing adverse reactions. It is suitable for local treatment of pain and inflammation such as ketoprofen.
Smart Images

Figure CN121059503A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biomedical materials, and particularly relates to a temperature / mechanical dual response type drug controlled release hydrogel and a preparation method thereof. BACKGROUND
[0002] Hydrogel is a kind of soft material with three-dimensional network structure and high water content. Because of its excellent biocompatibility and controllable physical and chemical properties, it has become an ideal candidate material in the field of drug delivery. In the traditional local drug release system, the release behavior of hydrogel is mainly limited by the diffusion of drugs and the degradation process of materials. Although the above mechanism can achieve the release of drugs to a certain extent, it often lacks sufficient precision and controllability, making it difficult to meet the clinical demand for efficient and safe delivery, thereby affecting the therapeutic effect. In recent years, intelligent response hydrogel has shown great potential in improving drug bioavailability and efficacy due to its controllable release capacity, stable and sustained release characteristics, and potential advantage of reducing drug administration frequency, and has attracted widespread attention. Such hydrogel can respond to external stimulus factors (such as pH, temperature, light, ultrasound and mechanical force), change its volume or internal structure, and thus realize the dynamic regulation of drug release. Compared with single stimulus response system, composite stimulus response hydrogel can respond to multiple external stimuli at the same time, providing more precise control of drug release in complex treatment environment. With the increasing diversification and complexity of clinical treatment needs, the limitations of single stimulus response system have become increasingly apparent, and the research and development of composite stimulus response hydrogel have emerged as the times require, and has become an important development direction in the field of intelligent drug delivery.
[0003] Ketoprofen is a widely used non-steroidal anti-inflammatory drug (NSAID) with good efficacy in relieving mild to moderate pain, inflammation and related diseases such as rheumatoid arthritis, osteoarthritis and gout. In addition, ketoprofen is also commonly used for the treatment of postoperative pain, traumatic pain and various other pain syndromes. Its main mechanism of action is to inhibit the activity of cyclooxygenase (COX-1 and COX-2), thereby inhibiting the synthesis of prostaglandins, and exerting a comprehensive therapeutic effect of anti-inflammatory, analgesic and antipyretic. Compared with common NSAIDs such as ibuprofen and diclofenac, ketoprofen shows stronger efficacy in analgesia and anti-inflammation. However, oral administration is still the most common way of ketoprofen administration, but long-term use may cause a series of adverse reactions, including gastrointestinal bleeding, ulcers, liver and kidney damage, and cardiovascular events (such as myocardial infarction). In contrast, topical preparations have been shown to significantly reduce systemic side effects while achieving similar therapeutic effects. Therefore, the development of intelligent drug delivery systems with controllable release function has become a research hotspot, aiming to improve therapeutic effect while minimizing adverse reactions. Among the many stimulus-responsive mechanisms, temperature and mechanical force are favored due to their good controllability and easy-to-operate characteristics. In particular, mechanical force is often closely related to analgesic scenarios, while elevated body temperature is accompanied by the need for antipyretic. Therefore, a hydrogel system based on a dual-response mechanism of temperature and mechanical force is expected to achieve more precise and efficient drug release regulation in the local delivery of ketoprofen, ultimately achieving optimized therapeutic effect. SUMMARY
[0004] This section is intended to summarize some aspects of the embodiments of the present application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of the specification to avoid obscuring the purpose of this section, the abstract and the title, and such simplifications or omissions are not used to limit the scope of the present application.
[0005] In view of the above and / or problems existing in the prior art, the present application is proposed.
[0006] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art and provide a preparation method of temperature / mechanical dual-responsive drug controlled-release hydrogel.
[0007] To solve the above technical problems, the present application provides the following technical solutions, comprising,
[0008] (1) dissolving NIPAm, AAc and crosslinking agent in water, degassing, adding SDS, heating to 65-75℃ for 0.5-1.5h, adding initiator, continuing to react for 3-5h, dialyzing to obtain MG microgel; adding EDC, HEMA and DMAP to MG microgel-water dispersion, stirring uniformly, dialyzing, freeze-drying to obtain vinyl-functionalized microgel (i.e. MGV microgel);
[0009] (2) dissolving MGV microgel and hydrophobic drug in organic solvent, then evaporating in vacuum for more than 3h, adding water, stirring in ice water bath overnight to obtain drug-loaded MGV microgel;
[0010] (3) mixing drug-loaded MGV microgel and NIPAm monomer uniformly in water, injecting nitrogen and aeration, adding initiator and accelerator to form hydrogel precursor, sealing and incubating to obtain drug-loaded MGV microgel crosslinked temperature / mechanical dual-responsive drug release hydrogel, denoted as NMK hydrogel.
[0011] As a preferred scheme of the preparation method of the temperature / mechanical dual-responsive drug release hydrogel, in the step (1), the crosslinking agent comprises MBAA and PEGDA.
[0012] As a preferred scheme of the preparation method of the temperature / mechanical dual-responsive drug release hydrogel, in the step (1), the mass ratio of NIPAm, AAc, crosslinking agent, SDS and initiator is 2.8-2.9: 0.20-0.21: 0.06-0.07: 0.11-0.12: 0.12-0.2.
[0013] As a preferred scheme of the preparation method of the temperature / mechanical dual-responsive drug release hydrogel, the mass ratio of EDC, HEMA and DMAP is 4.5-5: 3-3.8: 0.15-0.20.
[0014] The microgel concentration in the MGV microgel-water dispersion is 1-2wt.%
[0015] As a preferred scheme of the preparation method of the temperature / mechanical dual-responsive drug release hydrogel, the mass ratio of MGV microgel and hydrophobic drug is 300: 3-13; the mass / volume ratio of MGV microgel, organic solvent and water is 0.3g: 5-10mL: 5-10mL; the organic solvent comprises methanol and dimethyl sulfoxide.
[0016] As a preferred scheme of the preparation method of the temperature / mechanical dual-responsive drug release hydrogel, the hydrophobic drug comprises ketoprofen, paclitaxel, curcumin and doxorubicin.
[0017] As a preferred scheme of the preparation method of the temperature / mechanical dual response type drug controlled release hydrogel, in the application, the mass ratio of the drug-loaded MGV microgel and NIPAm monomer is 0.25-0.35:1.525-1.694.
[0018] As a preferred scheme of the preparation method of the temperature / mechanical dual response type drug controlled release hydrogel, in the application, the initiator includes potassium persulfate, ammonium persulfate (APS), and sodium persulfate (NaPS).
[0019] The accelerator includes tetramethyl ethylenediamine (TEMED).
[0020] As a preferred scheme of the preparation method of the temperature / mechanical dual response type drug controlled release hydrogel, in the application, the adding amount of the initiator in step (3) is 0.3-0.6 mg / mL. The adding amount of the accelerator is 1-3 μL / mL.
[0021] The purpose of the application is to overcome the deficiencies in the prior art, and provide a temperature / mechanical dual response type drug controlled release hydrogel, the compression strength of the hydrogel is 301.6-369.2 kPa.
[0022] The application has the following beneficial effects:
[0023] The application uses MGV microgel as a carrier of hydrophobic drugs, and uses the drug-loaded MGV microgel as a macromolecular crosslinking agent in the NIPAm crosslinking process, thereby preparing a hydrogel with fast response characteristics, and proposes a response mechanism of "temperature rise / compression-deformation-release". The hydrogel not only has excellent mechanical properties and good drug tissue permeability, but also has excellent biocompatibility, and can release the loaded drugs through temperature / mechanical dual response. As a transdermal drug preparation, it provides an innovative solution for clinical treatment of inflammation or pain, and provides a new idea for further development of intelligent drug delivery systems. BRIEF DESCRIPTION OF DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the application, the drawings needed in the embodiment description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor. Among them:
[0025] Figure 1 NM1K 13 NM2K 13 NM3K 13 NM4K13 Representative compressive stress-strain curves of hydrogels.
[0026] Figure 2 Drug loading properties of microgels: (a) Hydrodynamic diameter of MGV microgels with different ketoprofen contents. (b) Encapsulation efficiency of MGV microgels for different drug concentrations.
[0027] Figure 3 Mechanical properties of hydrogels: (a) NM3, NM3K 13 and NM3-K 13 Representative compressive stress-strain curves of hydrogels; (b), (c), and (d) represent NM3 and NM3K, respectively. 13 and NM3-K 13 Representative cyclic compressive stress-strain curves of hydrogels.
[0028] Figure 4 NM3, NM3K 13 and NM3-K 13 Representative differential scanning calorimetry (DSC) images of hydrogels.
[0029] Figure 5 NM3, NM3K 13 and NM3-K 13 Swelling and deswelling of hydrogels: (a) swelling properties at 25°C; (b) dehydration behavior at 37°C; (c) NM3, NM3K 13 and NM3-K 13 Dehydration behavior of hydrogels after soaking at different temperatures for 24 minutes.
[0030] Figure 6 Smart Response Drug Release Behavior of Hydrogels: (a) Schematic diagram of a test apparatus for evaluating drug release characteristics during hydrogel compression at controlled temperatures; (b) NM3-K 13 (c) Representative drug release curves at different temperatures; 13 (d) Representative drug release curves; NM3-K under different compressive strains and room temperature conditions. 13 Representative drug release curves; (e) and (f) NM3K 13 Representative drug release curves of hydrogels under the combined effects of temperature and mechanical force.
[0031] Figure 7 Representative small-angle X-ray scattering (SAXS) images of drug-loaded hydrogels under different compressive strains and temperatures.
[0032] Figure 8Hydrogel drug tissue permeability: (a) Schematic diagram of experimental device for evaluating drug permeation from hydrogel through mouse skin; (b) Ketoprofen release curve in mouse skin permeation experiment; (c) Schematic diagram of experimental device for evaluating drug permeation from hydrogel into pig skin; (d) Confocal fluorescence image of pig skin cross section after fluorescein permeation; (e) Statistical chart of fluorescein permeation depth from hydrogel into pig skin.
[0033] Figure 9 Hydrogel cell compatibility: (a) Relative cell viability of L929 cells cultured in hydrogel extract for 24 h; (b) Fluorescence image of live / dead staining treated L929 cells cultured in hydrogel extract for 3 days. DETAILED DESCRIPTION
[0034] In order to make the above objectives, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application are described in detail below in combination with the description examples.
[0035] In the following description, a large number of specific details are set forth in order to facilitate a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the connotation of the present application, therefore the present application is not limited by the specific examples disclosed below.
[0036] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an independent or alternative embodiment that excludes other embodiments.
[0037] The raw materials used in the present application are all ordinary commercially available materials without special instructions.
[0038] The abbreviations and their full names in the present application are as follows:
[0039] N-isopropyl acrylamide (NIPAm), acrylic acid (AAc), N,N'-methylene bisacrylamide (MBAA), polyethylene glycol diacrylate (PEGDA), sodium dodecyl sulfate (SDS), potassium persulfate (KPS), ammonium persulfate (APS), sodium persulfate (NaPS), poly (NIPAm-co-AAc) microgel (MG), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), hydroxyethyl methacrylate (HEMA), 4-dimethylaminopyridine (DMAP), vinyl-functionalized microgel (MGV), tetramethyl ethylene diamine (TEMED).
[0040] Example 1
[0041] The embodiment provides a preparation method of a temperature / mechanical dual response type ketoprofen controlled release hydrogel, in particular to the following:
[0042] 1) Preparation of MGV microgel: 2.848 g of NIPAm, 0.202 g of AAc and 0.064 g of MBAA were dissolved in 200 mL of deionized water, nitrogen was bubbled for 15 min, 0.116 g of SDS was added, and heated to 70 DEG C. After 1 h, 0.16 g of KPS was added to 4 mL of deionized water, and reacted for 4 h. After dialysis for 3 days, the MGV microgel was obtained. Then, 4.78 g of EDC, 3.64 g of HEMA and 0.17 g of DMAP were added to 100 mL of dispersion liquid containing about 1.5 g of MGV, and stirred at room temperature for 4 h. After dialysis for 3 days, the MGV microgel was obtained by freeze-drying.
[0043] 2) Preparation of drug-loaded MGV microgel: 0.3 g of the above MGV microgel and 13 mg of hydrophobic drug ketoprofen were dissolved in 5 mL of methanol, and stirred in an ice water bath for 30 min until completely dissolved, then evaporated in vacuum for more than 3 hours. Then, 5 mL of deionized water was added, and stirred in an ice water bath overnight to obtain ketoprofen-loaded MGV microgel, denoted as MGV-K 13 microgel. Note: K represents the drug, and the subscript 13 represents the mass of the drug (mg / 10 mL) in the MGV-K microgel. In the drug-loaded MGV microgel, the concentration of MGV is 3 wt%.
[0044] 3) Preparation of NM3K 13 hydrogel: 0.3 g of the above drug-loaded MGV-K 13 microgel was mixed with 1.5 mol / L of NIPAm monomer in 10 mL of deionized water, and continuously stirred for 1 h until uniformly mixed. Then, nitrogen was injected into the solution and aerated for 20 min, and 4.2 mg of potassium persulfate (KPS) was added as an initiator and 20 μL of tetramethyl ethylene diamine (TEMED) was added as an accelerator to form a hydrogel precursor. The precursor solution was injected into a closed glass mold, and incubated at room temperature for at least 48 h to obtain the NM3K 13 hydrogel. Note: N represents NIPAm, M represents MGV, and the subscript 3 represents the concentration (wt%) of MGV in the MGV-K microgel.
[0045] The mechanical test was performed on the NM3K 13 hydrogel, and the hydrogel was prepared into a cylindrical sample (diameter 9 mm, thickness 5 mm). A universal testing machine was used to compress the sample at room temperature at a strain rate of 10% per minute. The sample compression strength was 347.1 kPa, as Figure 1 shown.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that the concentration of MGV in the drug-loaded MGV microgel is adjusted to 2.5wt%, 2.8wt%, 3.2wt%, and 3.5wt%, respectively, and the rest of the preparation process is the same as that of embodiment 1 to prepare the hydrogel NMK. The mechanical test of the hydrogel shows that the compressive strength is 301.6kPa, 324.7kPa, 330.2kPa, and 309.6kPa, respectively.
[0048] The concentration of MGV has a significant effect on the compressive strength of the hydrogel. The drug-loaded MGV microgel acts as a macromolecular crosslinking agent in the NIPAm crosslinking process in the preparation of the hydrogel.
[0049] Embodiment 3
[0050] The difference between this embodiment and embodiment 1 is that the concentration of MGV in the drug-loaded MGV microgel is adjusted to 2.5wt%, the initiator is APS, the crosslinking agent is PEGDA, and the hydrophobic drug is paclitaxel, and the rest of the preparation process is the same as that of embodiment 1 to prepare paclitaxel-loaded MGV microgel NM 2.5 K 13 .
[0051] Embodiment 4
[0052] The difference between this embodiment and embodiment 1 is that the concentration of MGV in the drug-loaded MGV microgel is adjusted to 2.8wt%, the initiator is NaPS, and the hydrophobic drug is curcumin, and the rest of the preparation process is the same as that of embodiment 1 to prepare curcumin-loaded MGV microgel NM 2.8 K 13 .
[0053] Embodiment 5
[0054] The difference between this embodiment and embodiment 1 is that the concentration of MGV in the drug-loaded MGV microgel is adjusted to 3.2wt%, and the hydrophobic drug is ketoprofen, and the rest of the preparation process is the same as that of embodiment 1 to prepare ketoprofen-loaded MGV microgel NM 3.2 K 13 .
[0055] Embodiment 6
[0056] The difference between this embodiment and embodiment 1 is that the concentration of MGV in the drug-loaded MGV microgel is adjusted to 3.5wt%, the initiator is APS, the crosslinking agent is PEGDA, and the hydrophobic drug is paclitaxel, and the rest of the preparation process is the same as that of embodiment 1 to prepare paclitaxel-loaded MGV microgel NM 3.5 K 13 .
[0057] Embodiment 7
[0058] The difference between this example and Example 1 is that the amount of hydrophobic drug ketoprofen added is adjusted to 3, 5, 7, 9, 11, and 15 mg, respectively, and the rest of the preparation process is the same as that of Example 1 to prepare ketoprofen-loaded MGV microgels, which are denoted as MGV-K3, MGV-K5, MGV-K7, MGV-K9, MGV-K 11 11, and MGV-K 15 15, respectively.
[0059] The hydrodynamic particle size of MGV in the aqueous dispersion was characterized using a dynamic light scattering instrument. In addition, the aggregated ketoprofen was removed by low-temperature centrifugation (3600 rpm, 3 min) at 4°C using a Millipore ultrafiltration tube (15 mL, 10 kDa). The drug concentration in the filtrate was determined by a 260 nm ultraviolet-visible spectrophotometer, and the drug loading efficiency was calculated.
[0060] The results are shown in Figure 2 a. When the drug loading amount per 0.3 g of MGV increased from 3 mg to 11 mg (i.e., from MGV-K3 to MGV-K 11 ), the hydrated particle size distribution was obviously right-shifted, indicating that the particle size of the microgels gradually increased with the increase of the drug loading amount. However, when the drug loading amount reached 13 mg, the particle size distribution showed a bimodal pattern, and when the drug amount was further increased to 15 mg, the peaks were obviously separated. This indicates that when the drug loading capacity of the microgels reaches saturation, the excess drug is not effectively encapsulated.
[0061] Subsequently, the drug loading efficiency was quantitatively analyzed. The unencapsulated ketoprofen was removed by ultrafiltration using a Millipore ultrafiltration centrifuge tube under low-temperature conditions. As shown in Figure 2 b, when the drug loading amount increased from 3 mg to 13 mg, the encapsulation efficiency remained at a high level of more than 95%. However, when the drug loading amount was further increased to 15 mg, the encapsulation efficiency sharply decreased to 51.1%. This phenomenon indicates that the drug loading capacity of the MGV microgels has reached saturation at 13 mg.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that the concentration of MGV in the drug-loaded MGV microgels is adjusted to 2 wt% to prepare NM2K 13 . The hydrogel mechanical test is the same as that of Example 1, and the measured compression strength is 135.4 kPa, as shown in Figure 1 .
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 1 is that the concentration of MGV in the drug-loaded MGV microgels is adjusted to 4 wt% to prepare NM4K 13 . The hydrogel mechanical test is the same as Example 1, and the measured compressive strength is 248.8 kPa, as shown in Figure 1 .
[0066] As shown in Figure 1 , when the MGV concentration in the current body solution is increased from 2 wt% to 3 wt%, the mechanical properties of the hydrogel are significantly improved. Specifically, the compressive strength of the hydrogel is increased from 135.4 kPa of NM2K 13 to 347.1 kPa of NM3K 13 . This enhancement can be attributed to the synergistic effect of macro-crosslinkers during polymerization, which can include two aspects: first, the crosslinkers establish connections between polymer chains, thereby enhancing the toughness of the hydrogel; second, they induce internal crosslinking, thereby further improving the overall structural integrity of the hydrogel. However, when the MGV concentration is further increased from 3 wt% to 4 wt%, the compressive strength of the hydrogel decreases to 248.8 kPa. This can be due to the excessive amount of microgels, which increases the density of crosslinking points, thereby limiting the stretching of polymer chains during polymerization and reducing the mechanical strength of the hydrogel.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that the drug is directly dispersed into the mixture of MGV microgels and NIPAm monomers to prepare NM3-K 13 hydrogel through free radical polymerization. Specifically:
[0069] 0.3 g of MGV microgels and 1.5 mol / L of NIPAm monomers are mixed in 10 mL of deionized water and continuously stirred for 1 h until the mixture is uniform. Then, 13 mg of drug is directly dispersed into the mixture.
[0070] Performance Test Example 1
[0071] This test example investigates the effect of the drug on the hydrogel system, specifically:
[0072] Mechanical tests were performed on NM3, NM3K 13 , and NM3-K 13 hydrogels. The hydrogels were prepared into cylindrical samples (9 mm in diameter and 5 mm in thickness). A universal testing machine was used to compress the samples at a strain rate of 10% per minute at room temperature. The cyclic compression test was performed by applying and releasing a strain of 60% for 90 consecutive cycles. The energy dissipation during each cycle was quantified by calculating the enclosed area of the loading-unloading curve. The results are shown in Figure 3As shown in figure a, when the drug is loaded into the microgel and subsequently incorporated into the hydrogel, the mechanical properties decrease slightly, with a compressive strength of 374.1 ± 12.9 kPa, indicating that NM3K 13 Hydrogels possess sufficient strength to withstand the stress requirements that transdermal drug delivery formulations may face during use. When drugs are directly dispersed into the hydrogel system, NM3-K... 13 The mechanical properties of the hydrogel were significantly reduced, with a compressive strength of 162.2 ± 14.0 kPa.
[0073] Given that transdermal drug delivery systems are frequently subjected to mechanical forces, further research was conducted on NM3 and NM3K. 13 and NM3-K 13 The hydrogels underwent cyclic compression testing to evaluate their mechanical durability and structural stability. All three hydrogels exhibited excellent fatigue resistance during 90 load-unload cycles (0%–60%). Figure 3 (b~d). Among them, NM3 hydrogel exhibits the most outstanding fatigue resistance. The separation of the loading-unloading curves between cycles is the least obvious, and energy loss remains at a low level throughout. After 90 compression cycles, its energy dissipation is the lowest, approximately 0.05±0.01 MJ / m3. However, after the addition of the drug, the fatigue resistance of the hydrogel decreases, and NM3K... 13 and NM3-K 13 The energy dissipation of the hydrogel after 90 compression cycles was 0.14 ± 0.02 MJ / m. 3 and 0.17±0.01MJ / m 3 .
[0074] The above explains NM3K 13 Hydrogels exhibit good structural stability under repeated stress and have excellent fatigue resistance, enabling them to withstand the mechanical forces frequently encountered in transdermal drug delivery systems.
[0075] Performance Test Example 2
[0076] The LCST of the hydrogel was determined by differential scanning calorimetry (DSC). The DSC plots of the samples were obtained at a heating rate of 2 °C / min. The LCST of the hydrogel samples was determined by the peak values in the DSC curves.
[0077] like Figure 4 As shown, the LCST of NM3 hydrogel is 34℃; when the drug is directly dispersed in the hydrogel system, the LCST decreases most significantly, dropping to 31℃. The LCST of hydrogel prepared by loading the drug onto microgels drops to 32℃.
[0078] Performance Test Example 3
[0079] Hydrogel samples (9 mm in diameter, 2 mm thick) were immersed in 10 mL of deionized water and incubated at 25 °C until equilibrium was reached, and the swelling ratio was calculated. To investigate temperature-responsive dehydration behavior, the hydrogels were first swelled to equilibrium at 25 °C and then transferred to a preheated water bath (36–40 °C), and the dehydration ratio was calculated.
[0080] Below the lower critical dissolution temperature (LCST), the PNIPAM hydrogel is in a swollen state. For example... Figure 5 As shown in figure a, the swelling ratio of NM3 hydrogel at equilibrium is 345.6% at 25℃. After introducing hydrophobic drug molecules, NM3K... 13 and NM3-K 13 The decrease in network density of the hydrogel led to an increase in its swelling ratio to 435.5% and 570.9%, respectively. After the hydrogel swelled to equilibrium at 25°C, it was transferred to a water bath preheated to 37°C (T>LCST) to study its temperature-responsive dehydration behavior. Figure 5 As shown in b, all hydrogels exhibited significant dehydration under high-temperature stimulation, reaching equilibrium within approximately 24 minutes. With the introduction of the drug, the dehydration rate of NM3 hydrogel decreased slightly from 17.5% to NM3K. 13 16.8% of the hydrogel. However, in NM3-K 13 In the hydrogel, the direct dispersion of drug molecules within the hydrogel matrix interfered with the effective cross-linking between the PNIPAM polymer chains and the MGV microgel, resulting in a significant decrease in the dehydration ratio to 11.4%. Furthermore, as... Figure 5 As shown in Figure c, the dehydration ratio of the hydrogel system gradually increases with increasing temperature, exhibiting typical temperature-responsive behavior. However, NM3-K 13 Hydrogels exhibit anomalous temperature-dependent phase transitions during heating due to the steric hindrance effect caused by hydrophobic drug molecules within a three-dimensional network. These findings confirm the intelligent temperature-responsive properties of hydrogels and provide a theoretical basis for the development of temperature-sensitive intelligent drug-controlled release hydrogel systems.
[0081] Performance Test Example 4
[0082] The hydrogel sample (9 mm in diameter, 5 mm in thickness) was completely immersed in 15 mL of deionized water. At set time intervals, 3 mL of the extract was taken out for UV spectrophotometry, and an equal volume of deionized water was added to maintain a constant total volume. The cumulative release was calculated by measuring the drug concentration in the extract to evaluate the intelligent response drug release behavior of the hydrogel. The specific experiment was divided into the following three groups:
[0083] (1) Temperature-responsive drug release: The hydrogel samples were placed in room temperature environment and 37 °C constant temperature water bath respectively, and the difference of drug release behavior was observed under the same time conditions.
[0084] (2) Mechanical-responsive drug release: The hydrogel samples were placed in the center of a petri dish and completely immersed in water medium. Periodic compression force was applied using a universal material testing machine equipped with a custom-made clamp. The sample was initially attached to the bottom of the container and compressed at a constant rate of 3 s / mm until a strain of 40% or 60% relative to the initial thickness was reached, and then released at the same rate to restore the original structure. In the control group experiment, the loading module remained stationary and no strain was applied. After completing the preset number of compression cycles, 3 mL of solution was removed and an equal volume of fresh deionized water was added.
[0085] (3) Dual-responsive drug release: The experiment was conducted on the basis of the above compression device combined with a temperature control device Figure 6 a) The compression strain was set to 40% or 60%, and the environmental temperature was controlled at 25 °C or 37 °C. After completing the preset number of compression cycles, 3 mL of sample was removed and an equal volume of deionized water was added.
[0086] As shown in Figure 6 b, NM3-K 13 The drug release rate of the hydrogel was fast, and the release curve fluctuated significantly, with the drug reaching maximum release almost within 1-2 h, limiting its ability to achieve sustained release. Under heating conditions, a burst release phenomenon was also observed. Figure 6 c shows the drug release behavior of NM3K 13 hydrogels at temperatures below and above the LCST. At 25 °C, drug release mainly relied on passive diffusion within the microgel; when the temperature was raised to 37 °C or 40 °C, the MGV microgel and PNIPAM polymer chains contracted, resulting in a significant increase in drug release rate. After 3 h of release, the cumulative release of the drug was 306.4 ± 9.9 μg, 349.3 ± 4.8 μg, and 367.9 ± 12.4 μg at 25 °C, 37 °C, and 40 °C, respectively, showing a clear temperature-responsive release characteristic. After 6 h, the release increased further to 359.2 ± 12.8 μg, 368.0 ± 11.1 μg, and 376.8 ± 3.9 μg. Although the release difference at different temperatures gradually decreased, once the release reached equilibrium, the release at 37 °C and 40 °C was significantly higher than at 25 °C, and the release at 40 °C reached equilibrium the earliest.
[0087] Figure 6 d shows that when the drug was incorporated into the hydrogel in the form of direct dispersion, there was no obvious regularity in the drug release rate under 0%, 40%, and 60% compression strain conditions, and the total release amount did not exceed 190 μg. In contrast, as shown inFigure 6 As shown in FIG. 8E, if the drug was pre-encapsulated in the microgels before the hydrogels were formed, the drug release rate was relatively slow without external force, and the total release amount was about 174.6 ± 1.3 μg within 90 compression cycles. After applying mechanical force, the drug release amount increased significantly. At room temperature, when the compression strain was 40% and 60%, the cumulative release amount of the drug increased to 246.0 ± 31.6 μg and 313.7 ± 0.9 μg, respectively, after 90 compression cycles. Notably, no significant burst release of the drug was observed within the first 10 cycles, indicating that the system had good mechanical response control ability.
[0088] Figure 6 FIG. 8F further presents the effect of different compression strains on drug release at 37 °C. When the compression strain was 40%, the drug release amount was 360.7 ± 38.0 μg after 90 compression cycles. When the compression strain increased to 60%, the release amount reached 372.5 ± 4.2 μg after only 35 cycles. Compared with the results in FIG. 8E, the drug release rate was significantly accelerated, and the total release amount was significantly increased. These research results show that the hydrogel can achieve precise control of drug release by adjusting the strain, compression cycle, and temperature conditions. Figure 6
[0089] Performance Test Example 5
[0090] SAXS measurements were performed using a Xenocs GeniX 3D Cu ULD microbeam X-ray generator (wavelength: 0.154 nm). Two-dimensional SAXS patterns were obtained using a MAR345 X-ray detector, with a sample-to-detector distance of 3000 mm. The data acquisition time for each image was 300 seconds.
[0091] As shown in FIG. 8E, if the drug was pre-encapsulated in the microgels before the hydrogels were formed, the drug release rate was relatively slow without external force, and the total release amount was about 174.6 ± 1.3 μg within 90 compression cycles. After applying mechanical force, the drug release amount increased significantly. At room temperature, when the compression strain was 40% and 60%, the cumulative release amount of the drug increased to 246.0 ± 31.6 μg and 313.7 ± 0.9 μg, respectively, after 90 compression cycles. Notably, no significant burst release of the drug was observed within the first 10 cycles, indicating that the system had good mechanical response control ability. Figure 7 As shown, at 25 °C, no obvious morphological change of the microgels was observed when they were subjected to 40% or 60% compressive strain. However, when the temperature was raised to 37 °C, the same compressive conditions could induce the microgels to deform obviously along the compression axis. Small angle X-ray scattering (SAXS) test of the compressed hydrogels found that their scattering patterns changed from symmetric ring to elliptical two-dimensional pattern. This change could be attributed to the fact that the density difference between the poly(NIPAm-co-AAc) chains and the surrounding PNIPAM matrix was small at room temperature, which was below the sensitivity of SAXS detection; while at 37 °C, the difference in thermal expansion coefficient between the two increased, thus producing a more obvious density contrast, enabling SAXS to effectively detect this structural change. In the hydrogel system, the microgels, as energy dissipation units, deformed along the compression axis under the action of external mechanical force. This deformation destroyed the hydrophobic interactions within the microgels, weakened the encapsulation stability of the drug molecules, and promoted the release of the drug into the hydrogel matrix. Considering the good porous structure and high water content of the hydrogel, the released drug further diffused into the surrounding aqueous phase, thus realizing a sustained mechanical response drug release process.
[0092] In addition, under heating conditions, the PNIPAM chains changed from a loose structure to a tightly coiled conformation, making the internal environment of the hydrogel tend to be dense. In this restricted state, the microgels were more susceptible to compression deformation, thus further enhancing their stimulus-responsive drug release ability. In summary, the present application reveals the morphological changes of microgels under temperature and mechanical stimulation and their influence mechanism on drug release behavior, providing theoretical support and experimental evidence for the construction of intelligent hydrogels with high efficiency of stimulus response performance.
[0093] Performance test example 6
[0094] To evaluate the transdermal penetration performance of the drug in the skin, NM3K 13 The hydrogel (size: 1 cm x 1 cm x 2.4 mm, containing about 283 μg of ketoprofen) and the commercial patch A commercially available ketoprofen patch for pain relief (1 cm x 1 cm can provide about 285 μg of drug) was applied to the surface of the intact rat skin, respectively. Before use, the skin was first washed with normal saline, and the hydrogel was applied to the surface of the stratum corneum. The experimental system was placed in a constant temperature water bath at 37 ± 1 °C for incubation (see Figure 8 a). At the preset time points (2, 4, 6, 8, 10, 12 and 24 h), 1 mL of sample was taken from 5 mL of deionized water for analysis, and an equal volume of fresh deionized water was added to keep the system volume constant. The drug concentration was quantitatively determined by ultraviolet-visible spectrophotometry, and the cumulative penetration amount was calculated. In addition, the influence of temperature and mechanical stimulation on the transdermal penetration performance of the drug was further evaluated by fluorescence imaging.
[0095] AsFigure 8 b, the cumulative permeation amount of NM3K 13 The 24h cumulative permeation amount of ketoprofen released from the hydrogel was significantly lower than that of the commercial patch. However, at 37℃, the cumulative permeation amount of ketoprofen released from the NM3K 13 hydrogel was close to that of the commercial patch, and no significant difference was observed between them. This result indicated that ketoprofen released from the NM3K 13 hydrogel could effectively penetrate the skin, and the permeation in the skin tissue could be enhanced by increasing the temperature. The transdermal effect at 37℃ was comparable to that of the commercial product, further verifying the potential of the NM3K 13 hydrogel as an efficient carrier for ketoprofen.
[0096] Further, hydrophobic fluorescein was selected as a probe molecule and encapsulated in the hydrogel. The fluorescence distribution in the pig skin was detected to characterize the process of drug release from the hydrogel and permeation into the skin tissue (see Figure 8 c). As shown in Figure 8 d and 8e, the fluorescence penetration depth of the pig skin at 37℃ was significantly greater than that at 25℃, regardless of whether a compression force was applied. Meanwhile, the fluorescence signal at both 25℃ and 37℃ was significantly enhanced under a compression strain of 40%. Therefore, the dual-responsive characteristics of the hydrogel bring great prospects for the transdermal delivery of ketoprofen and other hydrophobic drugs.
[0097] Performance Test Example 7
[0098] In this study, mouse fibroblasts (L929) were used to evaluate the cytotoxicity of the hydrogel material. Briefly, 1 g of the hydrogel was soaked in 10 mL of complete DMEM medium (DMEM: fetal bovine serum (FBS): penicillin-streptomycin (100x) = 89:10:1) and incubated at 37℃ for 24 h to obtain the hydrogel extract. Subsequently, L929 cells were seeded in a 24-well plate at a density of 1×10 5 cells / well and cultured at 37℃ and 5% CO2 for 24 h. The original culture medium was then replaced with the corresponding hydrogel extract, and cells cultured with complete medium served as the control group. After 3 days of culture, cell viability was evaluated using live / dead cell staining, and the cell morphology and survival state were observed using a laser confocal scanning microscope. In addition, to further quantitatively analyze the relative viability of the cells, L929 cells were seeded in a 96-well plate at a density of 5×10 3 cells / well and cultured under the same conditions for 24 h. The corresponding hydrogel extract was then used to replace the culture medium, and the complete medium group served as the control group. Subsequently, the cell viability was determined using a CCK-8 kit.
[0099] The results showed that all experimental groups of cells had a high survival rate after 24 hours of culture. Figure 9 a) The relative survival rates all exceeded 85%, indicating that NM3 and NM3K 13 and NM3-K 13 The hydrogel exhibits good cell compatibility. Live / dead staining images obtained through laser confocal microscopy further confirmed that all experimental groups of cells displayed a typical spindle-shaped morphology, with green live cells dominating and only a small number of red dead cells. Figure 9 b). These results indicate that NM3, NM3K 13 and NM3-K 13 Hydrogels are non-cytotoxic and suitable as biocompatible materials for transdermal drug delivery systems.
[0100] In summary, the NM3K prepared by this invention... 13 Hydrogels possess excellent mechanical properties, intelligent responsiveness, and good biocompatibility, enabling precise control of drug release. They have broad application prospects in the field of transdermal drug delivery and provide innovative drug delivery solutions for the clinical treatment of inflammation and pain.
[0101] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a thermo-mechanical dual responsive drug controlled release hydrogel, characterized in that: The method comprises the following steps: (1) dissolving NIPAm, AAc and a cross-linking agent in water, adding SDS after degassing, heating to 65-75 DEG C and reacting for 0.5-1.5 h, adding an initiator, continuing to react for 3-5 h, and then dialyzing to obtain MG microgel; adding EDC, HEMA and DMAP to the MG microgel-water dispersion, stirring uniformly, dialyzing, and freeze-drying to obtain a vinyl-functionalized microgel, namely MGV microgel; (2) dissolving the MGV microgel and a hydrophobic drug in an organic solvent, then evaporating in vacuum for more than 3 h, adding water, and stirring in an ice water bath overnight to obtain drug-loaded MGV microgel; (3) mixing the drug-loaded MGV microgel and NIPAm monomers in water, injecting nitrogen and aerating, adding an initiator and an accelerator to form a hydrogel precursor, and sealing and incubating to obtain a drug-controlled release hydrogel with temperature / mechanical dual response, namely NMK hydrogel.
2. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The cross-linking agent in step (1) comprises MBAA and PEGDA.
3. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The mass ratio of NIPAm, AAc, the cross-linking agent, SDS and the initiator in step (1) is 2.8-2.9:0.20-0.21:0.06-0.07:0.11-0.12:0.12-0.
2.
4. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The mass ratio of EDC, HEMA and DMAP is 4.5-5:3-3.8:0.15-0.
20. The microgel concentration in the MG microgel-water dispersion is 1-2 wt.%.
5. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The mass ratio of the MGV microgel and the hydrophobic drug is 300:3-13; the mass / volume ratio of the MGV microgel, the organic solvent and water is 0.3 g:5-10 mL:5-10 mL; and the organic solvent comprises methanol and dimethyl sulfoxide.
6. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 5, characterized in that: The hydrophobic drug comprises ketoprofen, paclitaxel, curcumin and doxorubicin.
7. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The mass ratio of the drug-loaded MGV microgel and NIPAm monomers is 0.25-0.35:1.525-1.
694.
8. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The initiator comprises potassium persulfate, ammonium persulfate and sodium persulfate; and the accelerator comprises tetramethyl ethylenediamine.
9. The method for preparing the temperature / mechanical dual-responsive controlled-release hydrogel as described in claim 1, characterized in that: The addition amount of the initiator in step (3) is 0.3-0.6 mg / mL; and the addition amount of the accelerator is 1-3 μL / mL.
10. The thermo-mechanical dual responsive drug controlled release hydrogel prepared by the method according to any one of claims 1-9. The compression strength of the hydrogel is 301.6-347.1 kPa.